PEMANFAATAN TEKNOLOGI DIGITAL MARKETING DALAM UPAYA PUBLIKASI DAN PROMOSI DESA WISATA - Imam Husni Al Amin; Dewi Handayani U.N; Budi Hartono; Veronica Lusiana (ANDAN JEJAMA: Indonesian Journal of Community Engagement (IJCE), 2025)
The development of the region's potential encourages awareness that the area has the potential to become a tourist destination, especially in the form of a tourist village. In this regard, visionary and proactive figures are needed to unite all components of the community to collectively build and actively participate in attraction activities during tourist visits. The management of this effort is directed and organized by the community itself, and the youth, as initiators and movers, are equipped with skills to publicize and promote their tourist village using information technology, especially digital marketing.The utilization of digital marketing is a primary strategy in marketing and promoting the tourism potential of Desa Wisata Wonolopo. Information technology is used to disseminate information through social media and other digital platforms, so that the potential of Desa Wisata Wonolopo can be widely recognized by the public. The optimization of information technology usage, particularly through digital marketing, becomes a crucial means to promote and publicize Kampung Jamoe in the village of Wonolopo. This is particularly strategic in introducing the potential of traditional baby-carrying herbal products to a broader audience, with the hope of reviving the local economy in that area.